Representation of Uniformity in Persian and English Inflection Based on Dressler and Mayerthaler Approach: A Corpus-based Study - Leila Gholipour Hsasnkiadeh; Foroogh Kazemi (̒Ilm-i Zabān, 2022)
This study investigates the uniformity of Persian and English inflectional affixes based on Natural Morphology Theory to show how the uniformity of inflectional affixes of nouns, verbs, adjectives and adverbs can be explained. The present research has exercised mixed (qual-quan) and descriptive-analytical method. Research data were selected from both Persian and English corpora by the means of a random sampling method; afterward, the data were analyzed according to Dressler and Mayerthaler’s approach considering uniformity. In terms of frequency, the results identified uniformed forms in both languages and indicate that in the Persian corpus, 526 inflectional affixes of verbs, and all affixes of adjectives (185) are uniformed, although inflectional affixes of nouns lack uniformity. While in English corpus, inflectional verb affixes (89) represent uniformity, 172 inflectional noun affixes and 23 adjective affixes lack uniformity. Generally, the more frequency in uniformity of affixes shows they are less marked and more natural. Therefore, tense affix, negation, and subjunctive mood in the inflectional system are more natural than optative mood, past tense affix-ad, and imperative affix. Person and number markers are more natural than imperfect aspect in English. It is worth mentioning that all portmanteau morphs, suppletions and fusion forms reduce the naturalness of both languages due to the fact that there is no one-one relationship between their forms and meanings. The achievements of the current study can be useful in the field of translation studie